PENGARUH PENERAPAN STRATEGI THINK PAIR SHARE BERBANTUKAN MEDIA FOTO TERHADAP KETERAMPILAN MENULIS DESKRIPSI PADA SISWA KELAS II SD NEGERI 2 PULO REMBANG TAHUN PELAJARAN 2023/2024 - Himawan Angga Saputra; Qoriati Mushafanah; Asep Ardiyanto (STKIP Subang, 2023)
The background that drives this research is the low learning outcomes of students in Indonesian language subjects regarding descriptive writing skills. This is due to a lack of effective learning and less varied learning strategies and media. This research aims to determine the effect of the Think Pair Share strategy assisted by photo media in improving Indonesian language learning outcomes for class II description writing skills at SD Negeri 2 Pulo Rembang. This type of research is quantitative research using a Pre-Experimental Design approach, because this research is designed to only cover one group. The population in this study were all class II students at SD Negeri 2 Pulo Rembang. The sample for this research was 26 class II students at SD Negeri 2 Pulo Rembang using a sampling technique, namely Nonprobability Sampling. The data in this research was obtained through observation, interviews, documentation and tests. The collected data was then analyzed using the t-test, which was previously tested for initial and final normality. From the research results, the average pretest learning result score was 61.53 and the average posttest result score was 81.73. Based on the research results obtained, the average of pretest and posttest learning outcomes was then analyzed using the t-test, it was found that N= 26, the tcount value was 15.327 and db= 26 –2 = 24, so 24 was obtained with a significance level of 5%, the ttable was 2.064. tcount is 15.327 and ttable is 2.064. So the value of tcount > ttable (15.327 > 2.064), so that H0 is rejected and Ha is accepted. So there is a difference in the results of learning Indonesian for class II at SD Negeri 2 Pulo Rembang between before and after implementing the Think Pair Share strategy assisted by photo media. It can be concluded that the Think Pair Share strategy assisted by photo media has an influence in improving Indonesian language learning outcomes regarding description writing skills for class II at SD Negeri 2 Pulo Rembang. Based on the results of this research, the suggestion that can be made is that the Think Pair Share strategy assisted by photo media can be used as an alternative for teachers in teaching.